Between Strict and Flexibilty: A Comparative Insight of Qawa’id al-Fiqhiyyah in Islamic Banking Practices of Saudi Arabia and Pakistan - suparman, Suparman Kholil; Hersi, Mohammed (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose – This study aimed to analyze how Islamic legal maxims are implemented in the banking sectors of Saudi Arabia and Pakistan, with comparative insights from Indonesia and Malaysia Method – Using a qualitative comparative approach, this research examined fatwas, regulatory frameworks, and governance structures to assess the operationalization of key legal maxims such as al-umūr bi-maqāṣidihā (matters are judged by their objectives) and al-ḍarar yuzāl (there should be neither harming nor reciprocating harm).. Findings – Five working maxims—al-umūr bi-maqāṣidihā (purpose matters), al-yaqīn lā yazūlu bi-shakk (certainty prevails), al-mashaqqah tajlib al-taysīr (hardship begets facilitation), al-ḍarar yuzāl (harm must be removed), and al-ʿādah muḥakkamah (custom is authoritative)—explain cross-country variance. Saudi Arabia emphasizes textual rigor and documentary certainty, while Pakistan prioritizes contextual inclusion and adaptive tooling under the maqāṣid al-sharīʿah. Indonesia and Malaysia show a middle path through centralized fatwa governance and fintech-ready regulation. Practical implications – The study proposes a Q-ALIGN scorecard and a Maxim→Design→Control chain to translate fiqh maxims into auditable Shariah governance, consumer protection, and digital-era product controls, thereby advancing ḥifẓ al-māl and ḥifẓ al-ʿird, as well as the ESG governance agenda. Originality/value – The paper links classical maxims to concrete product and control choices across jurisdictions, clarifying how legal pluralism can remain ethically rigorous yet operationally resilient in modern Islamic banking